Biochanin A: A phytoestrogen with therapeutic potential. (September 2018) - Raheja, Shikha; Girdhar, Amit; Lather, Viney; Pandita, Deepti
Abstract: Background: Biochanin A, a bioactive constituent obtained from Trifolium pratense (red clover) and many other legumes, has drawn considerable attention of researchers in recent years owing to its wide spectrum of pharmacological activities. It exhibits multifaceted biological activities viz. neuroprotective, anticancer, anti-oxidant, anti-inflammatory, osteogenic, anti-hyperglycemic and protective effect on endothelial cell integrity and function. The therapeutic potential of this isoflavone has been explored in various in vitro, in vivo and ex vivo models. However, in vivo evidences are limited due to its low bioavailability. Scope and approach: This review highlights the therapeutic potential of biochanin A along with the methods of its extraction, isolation and identification, and supplemented further with approaches to enhance its bioavailability. The various molecular targets through which it displays different biological roles have also been spotlighted. Key findings and conclusion: Biochanin A, a potent molecule exhibits its molecular actions by targeting different phases of cell cycle; various signal transduction pathways involved in cell proliferation, cell differentiation, apoptosis, nuclear factor kappa B (NF-κB), and peroxisome proliferator-activated receptor gamma (PPAR γ). In cancer cells, biochanin A suppresses the activation of Akt and mitogen activated protein kinases (MAPKs) and also increases the expression of estrogen receptors (ERs) in other cellular models. Despite its huge potential, the clinical use of this isoflavone is limited due to its low bioavailability. Various strategies developed to enhance the bioavailability of biochanin A have led to foresee the potential of this promising molecule to increase the health benefits in future. Graphical abstract: Image 1 Highlights: Biochanin A has enormous therapeutic potential Methods of extraction and isolation have been reviewed Various molecular targets have been spotlighted Approaches to enhance solubility and bioavailability have been summarized